Economia solidária e geração de renda: uma análise das estratégias dos empreendimentos vinculados ao Centro de Referência Estadual de Economia Solidária - CRESOL/MA entre 2018 e 2022 - BECKMAN, Vanessa Geórgia Gonçalves Bastos (2023)
The present study focuses on solidarity-based enterprises linked to CRESOL in Maranhão, exploring their diversity and income-generating potential from 2018 to 2022. To underpin the research, theoretical frameworks were reviewed, and public policies were analyzed. The study adopts a methodology concerning its fundamental nature, qualitative approach, exploratory and descriptive objectives, and, in terms of procedures, relies on literature review along with the analysis of the main public policies supporting Solidarity Economy. Finally, the field research is conducted through interviews using a predetermined script with a semi-structured questionnaire comprising open and closed questions. The results indicate positive impacts on income generation and challenges such as sales seasonality and logistical obstacles. Solidarity Economy establishes itself as an alternative to the traditional development model, promoting values of solidarity and cooperation. Therefore, the research concludes that Solidarity Economy has a relevant impact on increasing the income generation of solidarity-based enterprises linked to CRESOL, involving a strengthening process of the local productive chain and valuing the developed local potential.